Improvementvoltage Stability and Load Ability Enhancement by Continuation Power Flow and Bifurcation Theory - Navid Ghaffarzadeh; Haniyeh Marefatjo; Iman Soltani; Fateme Salahian (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2013)
Power systems operation becomes more important as the load demand increases all over the world. This rapid increase in load demand forces power systems to operate near critical limits due to economic and environmental constraints. The objective in power systems operation is to serve energy with acceptable voltage and frequency to consumers at minimum cost. This paper studies the important power system phenomenon; voltage stability voltage stability is studies by using continuation power flow method and the effect of compensator, placement of generator and variation of line reactance on the voltage stability have been studied. Voltage collapse scenario is presented which can be a serious result of voltage instability and also the parameters that affected by voltage collapse are discussed. In analysing power system voltage stability, continuation power flow method is utilized which consists of successive load flows. This method is applied to a 14 bus sample test system and load-voltage curves for several buses are obtained. Simulation is done with PSAT in MATLAB. Continuation Power Flow was implemented using Newton-Raphson method. Simulation results show the proper performance of capacitor, variation of line reactance and placement of generator to improve voltage control on the lines and significantly increase the load ability margin of power systems.